Evaluation of bone development and organs in rat fetuses exposed to tartrazine - Osman Öztürk; Sümeyye Uçar; Züleyha Doğanyiğit; Aslı Okan Oflamaz; Evrim Suna Arıkan; Şükrü Ateş; Seher Yılmaz (Heliyon)
Tartrazine finds widespread application in the realms of alimentation, pharmaceuticals, cosmetic formulations, and textile manufacturing. Tartrazine has a negative effect on human health such as hyperactivity, allergies and asthma in children. Substances such as tartrazine might effect the embryo in a kind of aspects, containing physical or mental disorders, and a decrease in the child's intellectual memory. In this study, Sprague dawley female rats, 70–100 days old, weighing 250–300 g, with confirmed pregnancy, were divided into two groups of 5: control and tartrazine group. Rats were sacrificed on the 20th day and heart, lung, kidney and liver tissues were removed from the fetuses. The effect of tartrazine on fetal bone development was assessed by double skeletal staining, histological analysis on organs, and IL-6, IL-1β, TNF-α, and TRPM2 gene levels. It has been observed that tartrazine, which is frequently used as a food dye, damages important fetal tissues such as liver, kidney, lung and heart. A statistically meaningful reduce was observed in the total length, total area, bone length and bone area values of the limb bones in the tartrazine group compared to the control group (p < 0.05). It was observed that the mRNA levels of IL-6, IL-1β, TNF-α and TRPM2 genes in the livers of the fetuses changed compared to the control group (p < 0.05). In this study on the use of tartrazine during pregnancy, it was observed that both organs and bone development were damaged. More studies are needed on the effects of tartrazine.